Copepod Feeding Responses to Changes in Coccolithophore Size and Carbon Content - Jordan Toullec; Alice Delegrange; Adélaïde Perruchon; Gwendoline Duong; Vincent Cornille; Laurent Brutier; Michaël Hermoso (Journal of Marine Science and Engineering, 2022)
Phytoplankton stoichiometry and cell size could result from both phenology and environmental change. Zooplankton graze on primary producers, and this drives both the balance of the ecosystem and the biogeochemical cycles. In this study, we performed incubations with copepods and coccolithophores including different prey sizes and particulate carbon contents by considering phytoplankton biovolume concentration instead of chlorophyll a level (Chl a) as is usually performed in such studies. The egestion of fecal pellet and ingestion rates were estimated based on a gut fluorescence method. The latter was calibrated through the relationship between prey Chl a level and the biovolume of the cell. Chl a/biovolume ratio in phytopkanton has to be considered in the copepod gut fluorescent content method. Both coccolithophore biovolume and particulate inorganic/organic carbon ratios affect the food foraging by copepods. Finally, we observed a non-linear relationship between ingestion rates and fecal pellet egestion, due to the presence of calcite inside the copepod’s gut. These results illustrate that both prey size and stoichiometry need to be considered in copepod feeding dynamics, specifically regarding the process leading to the formation of fecal pellets.